IMPLEMENTATION OF CUSTOMARY LAW PRACTICES IN THE CUSTOMARY COMMUNITY OF KAMPUNG NAGA, TASIKMALAYA, WEST JAVA: CHALLENGES OF MODERNIZATION AND PRESERVATION STRATEGIES - Widya Noventari; Salsabila Kharisma Putri; Nurul Izah Qumairoh; Nimas Ayu Rutri Ami; Rida Nurhaliza; Rofi Rizky Ramadhan (PT. Radja Intercontinental Publishing, 2026)
The Kampung Naga indigenous community in Tasikmalaya is one of the Sundanese indigenous communities that still maintains customary law practices and traditional leadership patterns amidst the currents of modernization and the penetration of state law. This study aims to describe the implementation of customary law practices in Kampung Naga, analyze the challenges of modernization to the sustainability of customary law, and explore preservation strategies developed by the community and customary leaders. The study uses a qualitative approach with descriptive methods, through participatory observation, in-depth interviews with kuncen, lebe, punduh, formal government officials, and residents, as well as documentation and literature studies. The results of the study indicate that the customary leadership structure in Kampung Naga—centered on the kuncen and assisted by lebe and punduh who have strong traditional authority and work side by side with the formal government structure (hamlet head, RW, RT) in a relatively harmonious manner. The practice of customary law is centered on the philosophy of pamali (matak kabadi) which functions as a mechanism of social control, environmental protection, and character formation of residents, especially the younger generation. Modernization presents challenges in the form of technological penetration, intensified tourism, and demands for adjustments to national laws. However, indigenous communities have developed selective adaptation strategies through internal regulation, the integration of Islamic values, and the strengthening of oral transmission of customs to the younger generation. This study recommends strengthening the recognition of customary law through state policy, developing multicultural education that is sensitive to the rights of indigenous peoples, and partnerships between the state and indigenous communities in preserving the culture and environment of Kampung Naga.